Operatory metatekstowe w funkcji wskazówek organizacji tekstu w telewizyjnej relacji na żywo - Czoska, Agnieszka; Karaśkiewicz, Agata (Investigationes Linguisticae, 2012)
The article presents a study of the use of metatext markers for signalling the structure of television live report. The study is aimed at analysing how reporters organize their messages with metatextual elements. A corpus of live reports form polish news bulletins was used. The list of metatext markers was based on metadiscourse classifications by Hyland (2005), Dahl (2004) and Ädel (2006) and extended with propositions of the authors.